Molecular Docking for the Development of Alternative Therapies against Leishmaniasis - Guarimata, Juan Diego (2023)
Topoisomerases play a pivotal role in regulating the topological structure of DNA during fundamental processes such as transcription, DNA repair, or DNA replication; because of this, topoisomerases are biological targets in pathogenic microorganisms or malignant cells. In this study, we aimed to identify potential inhibitory compounds against topoisomerases type II of Leishmania mexicana via homology model and molecular docking. A comprehensive screening of 400 compounds provided by Medicines for Malaria Venture (MMV) in the Pandemic Response Box. Here, we identify the 20 best compounds against each topoisomerase type II of L. mexicana to identify new alternatives to treat a neglected tropical disease such as leishmaniasis.